Effect of bubble volume on the sweeping velocity of air bubbles in horizontal pipelines in water supply system - Hu, Jianyong; Yang, Chengzhi; Zhang, Yuzhou; Song, Hongge; Lu, Miao; Meng, Zhenzhu; Zhang, Jinxin (Frontiers in Earth Science, 2023)
Trapped air bubbles in pipelines significantly affect the safety and efficiency of water supply systems, potentially inducing water hammer and leading to pipeline explosions and interruptions. This study investigates the sweeping velocity of air bubbles in horizontal pipelines by analyzing the forces acting on a single air bubble and deriving a theoretical expression for calculating the sweeping velocity. Physical model experiments and numerical simulations are conducted to examine the variations in sweeping velocity with respect to bubble volume and dimensionless bubble volume. Results indicate that the sweeping velocity increases with bubble volume, and the diameter of the pipeline significantly affects the movement of air bubbles. These findings contribute to a better understanding of air bubble behavior in horizontal pipelines and can inform strategies for mitigating risks associated with trapped air bubbles, ultimately improving the safety and reliability of water supply systems.